2022
DOI: 10.1142/s0218348x22501900
|View full text |Cite
|
Sign up to set email alerts
|

Decoding of Heart–brain Relation by Complexity-Based Analysis of Heart Rate Variability (Hrv) and Electroencephalogram (Eeg) Signals

Abstract: Since the brain controls heart activations, there should be a correlation between their activities in different conditions. This study investigates the correlation between heart and brain responses to olfactory stimulation. We employed fractal theory and sample entropy to evaluate the complexity of EEG signals and Heart Rate Variability (HRV) in the form of R–R time series. We applied four different pleasant odors with different molecular complexities to 13 participants and analyzed their EEG and ECG signals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 70 publications
0
0
0
Order By: Relevance
“…Babini et al investigated the correlation between heart and brain responses collected from 5channel EEG and ECG sensors in response to four types of odors. They suggested that the odor complexity and variation cause an increase in the complexity of EEG and HRV [44]. Jiang et al conducted a study on the psychological effects of fragrant flowers by measuring EEG, pulse rate, and blood pressure [45].…”
Section: Relationship Between Olfactory Stimuli and Biological Signalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Babini et al investigated the correlation between heart and brain responses collected from 5channel EEG and ECG sensors in response to four types of odors. They suggested that the odor complexity and variation cause an increase in the complexity of EEG and HRV [44]. Jiang et al conducted a study on the psychological effects of fragrant flowers by measuring EEG, pulse rate, and blood pressure [45].…”
Section: Relationship Between Olfactory Stimuli and Biological Signalsmentioning
confidence: 99%
“…However, previous studies From the comparison between our study and previous studies that evaluated the psychological effect of olfactory stimuli using commercially available biological sensors, we obtained similar results from EEG and HRV analysis. However, previous studies [44][45][46][47] focused only on the psychological effect on the emotions expected by olfactory stimuli, such as the relaxing state after inhaling aromas. However, our study extended the interpretation of psychological effects through EEG and HRV indexes and applied them to the emotion map in corresponding to the existing emotion model like Russell's circumplex model of affect.…”
mentioning
confidence: 99%
“…Electrocardiography and electroencephalography are the main methods used to measure the physiological responses to odor exposure [4][5][6], and attempts have been made to use electrogastrograms (EGGs) [7]. In [7], no significant differences were noted in the frequency analysis of concentration differences during exposure to vanilla odor using EGGs; however, significant differences were found in the nonlinear analysis.…”
Section: Introductionmentioning
confidence: 99%